Ta/TiO2-and Nb/TiO2-Mixed Oxides as Efficient Solar Photocatalysts: Preparation, Characterization, and Photocatalytic Activity - Znad, Hussein; Ang, Ming; Tade, Moses (Hindawi Publishing Corporation, 2012)
Ta/TiO2- and Nb/TiO2-mixed oxides photocatalysts were prepared by simple impregnation method at different TiO2 : Nb or Ta mass ratios of 1 : 0.1, 1 : 0.5, and 1 : 1, followed by calcination at 500∘C. The prepared powders have been characterized by XRD, XPS, UV-Vis spectra, and SEM. The photocatalytic activity was evaluated under natural solar light for decolorization and mineralization of azo dye Orange II solution. The results showed that Nb/TiO2- and Ta/TiO2-mixed oxides have higher activity than the untreated TiO2 under natural solar light. The maximum activity was observed for Nb/TiO2 sample (at mass ratio of 1 : 0.1), which is characterized by the smallest crystalline size (17.79 nm). Comparing with the untreated TiO2, the solar decolorization and mineralization rates improved by about 140% and 237%, respectively, and the band gap reduced to 2.80 eV. The results suggest that the crystal lattices of TiO2 powder are locally distorted by incorporating Nb5+ species into TiO2, forming a new band energy structure, which is responsible for the absorption in the visible region. Unlike Ta/TiO2, the Nb/TiO2-mixed oxides can prevent the grain size growth of the treated TiO2, which is important to achieve high solar photoactivity.